Development of a Constructivist-Oriented Teaching Module with Mind Maps for High School Biology Learning on the Excretory System - Nengsih, Rodiantifitri; Qadariah, Nosi; Putri, Rahayu Dian Eka (Fakultas Tarbiyah dan Ilmu Keguruan UIN Jurai Siwo, Lampung, 2024)
One of the efforts to bridge students' activities in constructing their knowledge is through constructivist-oriented modules equipped with mind maps. This research aims to develop a constructivist-oriented module with mind maps for the topic of the excretory system and to assess the validity, practicality, and effectiveness of the developed learning module. This study is a development research that employs the Four-D Models, which include the stages of Definition, Design, Development, and Dissemination, though the dissemination stage was not carried out. The results indicate that the constructivist-oriented module equipped with mind maps is valid, practical, and effective. The average module validation score is 3.54, the average practical test score by teachers is 3.23, the average practical test score by students is 3.54, and the effectiveness of the module can be observed from students' motivation, activity, and learning outcomes.